PRINSIP-PRINSIP KEPEMILIKAN SAHAM PEMERINTAH DALAM PERUSAHAAN MILIK NEGARA (STUDI PERBANDINGAN ANTARA INDONESIA DENGAN SINGAPURA) - Aryanti, Ni Wayan Desi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2014)
This  journal  entitled  “Comparative  Study  Concerning  The  Principles  of  Government’s Shares in State Owned  Enterprise”.  Problems  being research  in this thesis are, first: the legal standing of the state’s equity in Persero according to Indonesian corporate law and its comparison to Singapore corporate law. The second problem, what are legal implications of the government’s shares in Persero. The  method  being  used  is  normative  legal  research  through  legislation  and  regulation a p p r oa c h  and  comparative  approach.  Legal  materials  used  are  primary  legal  materials, legal materials and secondary and tertiary legal materials, the analysis done by descriptive, evaluative, interpretative, analytical and argumentative. This research shows that according  to Indonesian  corporate law, the state’s equity being p laced in Persero   belongs to Persero and according to Singapore Law, the government’s equity being  placed  in  Persero  as the Government  Linked  Company  belongs  to the said company.  Legal consequences of the government equity in Persero are: the management of the said equity is no longer subject to state budget’s principals but to good corporate government principals; contracts made by Persero binds Persero and not the government, hence compliance and liability arising from the said contracts are Persero’s liability only and therefore Persero’s claim arising from contracts belong to the said Persero. However, in practical level, there are still some inconsistency in Persero’s equity treatment (i.e. financial audit and Persero’s inability to act as the guarantor to another company). On  the  other  side,  the  Government  of  Singapore’s  equity  in  Temasek  is  managed  by corporate mechanism and almost without government intervention (except for past reserves). Therefore  Temasek  is  free  to  make  any  contract  with  third  parties  and  can  act  as  the guarantor for its subsidiary.
Keywords: State’s Equity; Persero; Government Linked Company; Temasek